Desain Gaji Pokok menggunakan Metode Point System pada UKM Katering di Kota Bekasi - Melli Tiani; Yogi Wangsa; Muhammad Izzul Hakim; Bagoes Cahyo Alyadiansyah; Lindawati Kartika (Syntax Idea)
Compensation is one important factor that can motivate employees to improve performance. The compensation given by the company must be commensurate with the company's workload, job risks, and the competencies that accompany the position. The company is obliged to provide both financial and non-financial compensation so that the employees' standard of living needs (KHL) can be met. Therefore, it is necessary to design an appropriate compensation system based on job value. The object of this research is UKM Catering located in Bekasi City. UKM Catering is engaged in the culinary field, which focuses on the catering sector. The research methods used are quantitative and qualitative methods based on trusted scientific journals and articles. This research focuses on the compensation system and standard of living needs of UKM Catering employees. The data processing and analysis method used to develop a job value-based compensation system and job grading in Catering UKM is using Compensable Factors analysis using Adhered Salary Mapping, Salary Mapping Overlapping. The results of this study indicate that an effective compensation system to be implemented by Catering UKM is by using the Overlapping method. This is because the overlapping method of salary distribution is more profitable because the salary increase is not as big as the adhered method.